Vestígios do meu corpo: Uma investigação sobre a visibilidade da performance na arte contemporânea - JÉSSICA LACERDA (2023)
This dissertation aims to investigate the processes of signification linked to performance in contemporary art, in which the body participates as a means, a guide to the process, and an artistic product, becoming an important axis of artistic propositions about the present body. To do so, I support my research on theoretical studies about performance and the body as a mediation for experiencing the world and producing meaning; these are taken as the basis for a brief study on a set of selected works as a corpus for analyzing their relationship with the artist-body. Initially, for the theoretical studies on performance, we turn to scholars Jorge Glusberg (2013), Renato Cohen (2013), Roselee Goldberg (2015), Regina Melim (2008), Giulio Carlo Argan (1992), and Michael Archer (2012), as well as other theorists that allowed us to conduct a reflection on the subject. To reflect on the processes of experiencing the world through the body, at first, we seek theoretical support in studies on art as an experience by John Dewey (1859-1952), in the phenomenology of Charles Sanders Peirce (1839-1914), as it appears in the studies of Ivo Assad Ibri (2015), as well as in studies on the body by Maurice Merleau-Ponty (1908-1961), Christine Greiner (2005), and Henri-Pierre Jeudy (2002). In a second moment, we consider the potentialities of the body as a space of/for the construction of meaning, with the contribution of Peirce's general semiotics. Finally, to delve into the investigation of performance as a means of signifying organization that operates through the artist's body to create new meanings, we selected three artists: Priscilla Pessoa, Carolee Schneemann, and Gillian Wearing, using some of their works as the corpus of analysis, allowing us to explore relevant elements about the relationship with the body and performance. The analyses are grounded in the studied theoretical framework and Peircean semiotics, as well as the concept of visibility, introduced by Lucrécia D’Alessio Ferrara (2002). The results encourage an expanded understanding of the body-artist relationship and performance, as well as enabling further investigations related to contemporary art and semiotics.